Development of Basic Rusal Services: An Operational Approach - Sutanto, Agus; Umrotun, U (Universitas Muhammadiyah Surakarta, 1991)
Approach on the study of rural service development is often confused with general regional development study in which both development indicators are interchanged. However the two study are closely related and able to contribute one to another. A confusion also exist in the setting up of the concepts of social services, economic services, and infrastructures functions. As such, the study of service development should have a great care of the study implication inÂ which sectoral action planning should follow up. This article tries to present an operational approach on the rural service development with an ilustrative case study of Yogyakarta Special Region.